Application of Clinical Databases to Contemporary Cardiac Surgery Practice: Where are We now? - Saxena, Akshat; Newcomb, Andrew E.; Dhurandhar, Vikrant; Bannon, Paul G. (Heart, lung & circulation, 2016)
Cardiac surgery has embraced and encouraged the use of large, multi-institutional datasets in clinical practice. From a research perspective, database studies have facilitated an increased understanding of cardiac surgery. Among other uses, they have allowed an investigation of disease incidence and mortality, high risk groups, disparities in health care delivery and the impact of new devices and techniques. Databases are also important tools for clinical governance and quality improvement. Despite their obvious utility, clinical databases have limitations; they are subject to treatment bias, contain missing data and cannot establish causality. Moreover, the ongoing maintenance of the database requires significant human and financial resources. In the future, inclusion of more detailed follow-up data and integration with other datasets will improve the utility of clinical databases.